Criminal and civil identification with DNA databases using bayesian networks - Andrade, M.; Ferreira, M. A. M. (International Journal of Security, 2009)
Forensic identification problems are examples in which the study of DNA profiles is a common approach. To deal with these problems an introduction and explanation of various concepts is needed. Here we present some problems and develop their treatment putting the focus in the use of object-oriented Bayesian networks. The use of DNA databases, which began in 1995 in England, has created new challenges about its use. In Portugal the legislation for the construction of a genetic database was defined in 2008. With this it is important to determine how to use it in an appropriate way. For a crime that has been committed, forensic laboratories identify genetic characteristics in order to connect one or more individuals to it. Apart the laboratories results it is a matter of great importance to quantify the information obtained, i.e., to know how to evaluate and interpret the results obtained providing support to the judicial system. Other forensic identification problems are body identification; whether the identification of a body (or more than one) found, together with the information of missing persons belonging to one or more known families, for which there may be information of family members who claimed the disappearance. In this work intend to discuss how to use the database; the hypotheses of interest and the database use to determine the likelihood ratios, i.e., how to evaluate the evidence for different situations. Keywords: Bayesian networks, DNA profiles, identification problems.